A qualitative analysis of novice and expert mental performance consultants' professional philosophies. Issue 3 (3rd July 2023) - Castillo, Elmer A.; Block, Carly J.; Bird, Matthew D.; Chow, Graig M.
Abstract: Professional philosophy has received increased attention as a topic of research and applied interest. A professional philosophy is believed to develop during the early years of consulting and evolve as a function of experience, advanced education and training, reflective practice, and supervision. To systematically investigate this proposed transition, this study sought to analyze novice and expert mental performance consultants' (MPCs) professional philosophies using Poczwardowski et al.'s hierarchical structure of professional philosophy as a guiding framework. Additionally, this study aimed to explore perceptions of how a professional philosophy might improve consultant effectiveness. Eighteen participants (9 novice MPCs, 9 expert MPCs) were interviewed about the various components of their professional philosophy. Findings revealed key similarities and differences between the types of philosophies that novice and expert MPCs adopted in their practice. Novice and expert consultants exuded their values in the relationships with their clients, however, experts modeled their values through their behaviors. Although both groups used their chosen theoretical paradigm to guide their work with clients, expert MPCs specifically mentioned using this to aid their case conceptualization. Benefits of understanding one's unique philosophy to provide sport psychology services were also highlighted by both groups. Findings help to further highlight the importance of developing a consulting philosophy as a novice consultant. Furthermore, understanding one's philosophical approach to practice could be important for ensuring seasoned consultants are providing effective services to clients. Lay summary: Professional philosophy is a fundamental driving force of mental performance service delivery and represents a valuable asset for both junior and senior practitioners. Professional philosophy is characterized by the purpose, values, beliefs, and ideals underlying one's consulting approach and underpins the decisions regarding which theories, principles, interventions and techniques to utilize in practice to facilitate change. Based on the nuances observed when comparing philosophies of novice and expert mental performance consultants, practitioners of all levels can benefit from periodically reflecting upon their consulting philosophy to continuously hone their craft and improve their competence and efficacy. IMPLICATIONS FOR PRACTICE: Novice mental performance consultants should look to develop a philosophy in line with their values and beliefs at an early stage in their career. Expert consultants should continue to be aware of their own philosophy and recognize the importance of how it contributes to an effective and coherent delivery of service.